Prevalence of dentomaxillary anomalies in primary and mixed first phase dentition in the Faculty of Dentistry of the University of Chile, 2018 - Campos Pardo, Mauricio (2019)
Objetive. The present study aimed to analyze the prevalence of dentomaxillary anomalies in children aged 3 to 10 years old who requested attention at the Faculty of Dentistry of the University of Chile in the year 2018. Methods. A descriptive and cross-sectional study was carried out, where the universe corresponded to the patients attended in the SWU (Student Work Unit) of the Child and Adolescent Clinic of the 4th year of the Faculty of Dentistry of the University of Chile. Cohort 2018. For the evaluation of dentomaxillary anomalies, the Modified Bonn Biogenetic Classification was considered. Intermaxillary abnormalities. Results. Of the total sample analyzed (n: 106), 45.1% of the patients presented transverse, vertical and/or sagittal type alterations. Conclusions. The most prevalent transversal anomaly was the unilateral cross bite. The most prevalent vertical anomaly was the deep bite. The most prevalent sagittal anomalies were the distoclusions and the simple Inverted bite.